Augmented Reality-Based Flipbook sebagai Inovasi Media Pembelajaran Biologi: (Augmented Reality-Based Flipbook as Biology Learning Media Innovation) - Aisyah Zumira; Fitriani Nurzeha; Rohwan Maulana Luthfi; Riandi Riandi; Ari Widodo (BIODIK, 2022)
21st century skills require students to have skills such as creative thinking skills, critical thinking and problem solving, communication, and collaboration. With these skills, students are expected to be able to compete and survive through life changes in the future. Learning media is one of the learning tools provided by the teacher to facilitate students understanding the learning content. Innovative learning media is expected to reduce learning loss during the pandemic. One of the learning media that is expected to create an interesting, conducive learning atmosphere, and be able to transfer learning materials easily and efficiently is flipbook media. The aims of this research aremaking a flipbook based on augmented reality as one of the biology learning media. The research method used is a literature review or literature study. The references used focus on biology learning media, flipbooks, augmented reality, and biology learning media innovations. The research articles used are the results of research within the last 10 years. The research data were analyzed descriptively and qualitatively. The result of this research is an innovation of biology learning media, namely an augmented reality-based flipbook. Key words: augmented reality, flipbook, biology Â  ABSTRAK Keterampilan abad 21 menuntut peserta didik untuk memiliki kecakapan seperti keterampilan berpikir kreatif, berpikir kritis dan pemecahan masalah, berkomunikasi, dan berkolaborasi. Dengan keterampilan tersebut, peserta didik diharapkan dapat bersaing dan bertahan melalui perubahan kehidupan kedepannya. Media pembelajaran merupakan salah satu alat belajar yang disediakan guru untuk memfasilitasi siswa memahami konten pembelajaran. Media pembelajaran yang inovatif diharapkan dapat mengurangi learning loss selama masa pandemi. Salah satu media pembelajaran yang diharapkan dapat menciptakan suasana belajar yang menarik, kondusif, serta bisa mentransfer materi pembelajaran secara mudah dan efisien yaitu media flipbook. Tujuan penelitian ini yaitu pembuatan flipbook berbasis augmented reality sebagai salah satu media pembelajaran biologi. Metode penelitian yang digunakan adalah kajian pustaka atau study literature. Referensi yang digunakan berfokus pada media pembelajaran biologi, flipbook, augmented reality, dan inovasi media pembelajaran biologi. Artikel penelitian yang digunakan merupakan hasil penelitian dalam kurun waktu 10 tahun terakhir. Data hasil penelitian dianalisis secara deskriptif kualitatif. Hasil penelitian ini adalah inovasi media pembelajaran biologi, yaitu flipbook berbasis augmented reality (augmented reality-based flipbook). Kata kunci: augmented reality, flipbook, biologi